The special pecularities and construction systems of Ottoman Turkish house examples especially in Antalya, Isparta and Burdur - Urfalioglu, N (WIDE DREAMS PROJECTOS MULTIMEDIA LDA, 2002)
Ottoman-Turkish house examples can be seen in a wide spreading throughout the Balkan Peninsula and Anatolia. Today, there are a lot of Ottoman-Turkish house examples, which are older than 200-250 years old, in Greece, Albania, Macedonia, Bulgaria and in Turkey. However, they have got similar pecularities with each other, there are some different types among regions because of their users or climate. Ottoman society has got different ethnic groups such as Muslims, Greeks, Jewish etc. The houses of these communities have got different pecularities on some points. These cities of Antalya, Isparta and Burdur are on the Mediterranean Region of Turkey. They also had different communities during, the Ottoman period.
Keywords: Ottoman Turkish house; timber skeleton system; Ottoman measurement system; Himis; Muskali; Architecture; Construction & Building Technology; Engineering; Environmental Sciences & Ecology; Urban Studies